Polyphenylene ether melt extrusion product and method for producing polyphenylene ether melt extrusion product
By introducing a fracture structure and a melting extrusion process with high helical rotation rate into the polyphenylene ether, the problems of fluidity and processability of polyphenylene ether in the prior art are solved, and high-performance melt forming and the manufacturing of fine yarn molten fibers are achieved.
Patent Information
- Application Number
- JP2023147738
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-24
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-09-18
Smart Images

Figure 0007647824000017 
Figure 0007647824000001 
Figure 0007647824000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyphenylene ether melt extrusion product containing a polyphenylene ether component having a rearrangement structure, and a method for producing the polyphenylene ether melt extrusion product. [Background technology]
[0002] Polyphenylene ether (hereinafter sometimes referred to as PPE) has excellent heat resistance, flame retardancy, strength, chemical resistance, etc., and thus molded articles made from polyphenylene ether are used in a wide range of fields. However, polyphenylene ether generally has a high melt viscosity, so melt molding of polyphenylene ether alone or with a high polyphenylene ether content is difficult, and it is particularly difficult to melt spin it into fibers.
[0003] Known melt-spun fibers containing polyphenylene ether include those obtained by melt-spinning a polymer alloy of a non-crystalline thermoplastic resin such as polyphenylene ether and a crystalline thermoplastic resin such as polypropylene (see, for example, Patent Document 1), fibers containing polyphenylene ether and a processing aid and a flame retardant containing linear low-density polyethylene, petroleum resin, or a combination thereof (see, for example, Patent Document 2), and fibers made of a polyphenylene ether-based resin composition made of polyphenylene ether and a copolymer having a functional group reactive with polyphenylene ether (see, for example, Patent Document 3). Also known is a composition containing two types of polyphenylene ether resins having a specific intrinsic viscosity (see, for example, Patent Document 4). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-190156 A [Patent Document 2] Special Publication No. 2017-502179 [Patent Document 3] JP 2008-138294 A [Patent Document 4] Special Publication No. 2003-531234 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in Patent Documents 1 and 2, crystalline thermoplastic resins such as polypropylene, processing aids, etc. are added to polyphenylene ether to improve processability, and the polyphenylene ether content is low, so the excellent characteristics of polyphenylene ether cannot be fully utilized. Furthermore, in Patent Document 3, although the polyphenylene ether content is high, only thick fibers with a diameter of 0.14 mm are obtained, and it is considered that the fluidity of polyphenylene ether is not sufficiently improved. In Patent Document 4, a polyphenylene ether blend with high fluidity is obtained by including two types of polyphenylene ether resins with different intrinsic viscosities. That is, in these documents, some material is added to polyphenylene ether or the intrinsic viscosity is adjusted to improve processability and fluidity, and there is no consideration at all about improving processability by giving polyphenylene ether a rearrangement structure.
[0006] An object of the present invention is to provide a polyphenylene ether melt-extrusion molded product which can be melt-molded without mixing with other resin components and which has excellent properties such as mechanical strength, and a method for producing the polyphenylene ether melt-extrusion molded product. [Means for solving the problem]
[0007] Means of the Invention The present inventors have conducted extensive research into melt extrusion molding of polyphenylene ether and have found that the above-mentioned problems can be solved by using a polyphenylene ether component having a specific rearrangement structure, thereby completing the present invention.
[0008] That is, the present invention relates to a polyphenylene ether melt extrusion molded product characterized in that it contains a polyphenylene ether component having a rearrangement structure with continuous ortho-position bonds in repeating units with continuous para-position bonds.
[0009] The repeating units connected consecutively at the para position are represented by the following general formula (1): [ka] (In the formula, R 1 , R 2 are each independently a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, R 3 each independently represents a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent. The rearrangement structure is a repeating unit represented by the following general formula (2): [ka] (In the formula, R 1 , R 2 are each independently a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, R 3 each independently represents a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, R 3’ R 3 represents a divalent group in which one hydrogen atom has been removed from It is preferable that the structure is represented by the following formula:
[0010] The amount of rearrangements in the polyphenylene ether component having the rearrangement structure is preferably 0.1 mol % or more based on the total polyphenylene ether structural units in the polyphenylene ether component.
[0011] The content of the polyphenylene ether component is preferably 95% by mass or more of all the components forming the molded article.
[0012] The rearrangement structure is shown by nuclear magnetic resonance spectrum ( 1In 1 H-NMR measurement, it is preferable that the compound shows peaks in the range of 6.8 to 7.0 ppm and in the range of 3.8 to 4.0 ppm.
[0013] The polyphenylene ether melt extrusion molded product preferably has a glass transition temperature of 190°C or higher and 210°C or lower.
[0014] The polyphenylene ether melt extrudate is preferably a polyphenylene ether melt spun fiber.
[0015] The polyphenylene ether melt spun fiber preferably has a single fiber fineness of 1.0 dtex or more and 100 dtex or less.
[0016] The polyphenylene ether melt spun fibers are preferably staple fibers.
[0017] The short fibers are preferably flame-retardant short fibers.
[0018] The polyphenylene ether melt extrudate is preferably a paper formed from the polyphenylene ether melt spun fibers.
[0019] The paper is preferably flame-retardant paper.
[0020] The polyphenylene ether melt extrudate is preferably a fabric formed from the polyphenylene ether melt spun fibers.
[0021] The fabric is preferably a flame-retardant fabric.
[0022] The polyphenylene ether melt extrusion molded product is preferably a film.
[0023] The film is preferably a flame-resistant film.
[0024] The present invention also relates to a method for producing a polyphenylene ether melt extrusion molded product, comprising the step of melt-extruding a raw material, polyphenylene ether, at a peripheral speed of the screw of 3.6 m / min or more using an extruder equipped with a cylinder and a screw.
[0025] The temperature inside the cylinder is preferably 250 to 350°C.
[0026] The raw material polyphenylene ether preferably contains polyphenylene ether having a glass transition temperature of 170° C. or higher.
[0027] The raw material polyphenylene ether may further contain polyphenylene ether having a glass transition temperature of less than 170°C.
[0028] It is preferable that the polyphenylene ether melt extrusion molded product is a polyphenylene ether melt spun fiber, and that the melt extruding step is followed by a step of discharging the molten polyphenylene ether from a spinning nozzle and spinning the same.
[0029] The output rate per hole of the spinning nozzle is preferably 0.4 g / min or less, and in order to obtain fibers with a single yarn fineness of 15 dtex or less, it is preferably 0.2 g / min or less. Effect of the Invention
[0030] The present invention uses a polyphenylene ether component having a rearrangement structure, so that melt molding is possible, and a polyphenylene ether melt extrusion molded product having excellent mechanical strength and the like can be formed, and furthermore, it is possible to form melt spun fibers, which are more difficult to produce. The polyphenylene ether melt extrusion molded product of the present invention is excellent not only in mechanical strength, but also in flame retardancy, heat resistance, chemical resistance, and the like. Furthermore, according to the production method of the present invention, the molecular chain of the raw material polyphenylene ether is cut by melt extrusion at a high screw rotation speed, and a rearrangement reaction occurs, so that the fluidity of the polyphenylene ether is significantly improved, and a polyphenylene ether melt extrusion molded product can be formed. Furthermore, the melt molded product obtained by the production method of the present invention is formed of polyphenylene ether having a higher molecular weight than the raw material polyphenylene ether, and therefore has a characteristic that the glass transition temperature is relatively high. Furthermore, according to the production method of the present invention, a rearrangement reaction of polyphenylene ether occurs in the melt extrusion step, so that melt molding is possible. [Brief description of the drawings]
[0031] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic diagram of one embodiment of a method for producing a polyphenylene ether melt-extrusion molded product of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] Polyphenylene ether melt extrusion molding The polyphenylene ether melt extrusion molded product of the present invention is characterized in that it contains a polyphenylene ether component having a rearrangement structure at an ortho position in a repeating unit that is continuous at a para position. Here, the "rearrangement structure at an ortho position" refers to a structure in which a continuous side chain is formed by bonding at an ortho position to a part of the repeating units that are continuous at a para position in the main chain, and the side chain may be formed from repeating units that are continuous at a para position, and may also have a part that is partially bonded at an ortho position.
[0033] The repeating units successively connected at the para position include those represented by the following general formula (1): [ka] (In the formula, R 1 , R 2 are each independently a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, R 3 each independently represents a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent. The rearrangement structure is preferably a repeating unit represented by the following general formula (2): [ka] (In the formula, R 1 , R 2 are each independently a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, R 3 each independently represents a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, R 3’ R 3 represents a divalent group in which one hydrogen atom has been removed from It is preferable that the compound has a rearrangement structure represented by the following formula: In the general formula (2), "~" indicates that the structure following it is not particularly limited. The portion "~" may be formed from consecutive phenylene ether units with para-bonds, and may also partially contain a portion bonded at the ortho position.
[0034] The rearrangement reaction is, for example, a reaction represented by the following formula: [ka] This reaction is sometimes called the methylene bridge rearrangement.
[0035] Generally, polyphenylene ether has a high melt viscosity, and it has been considered difficult to melt mold when it contains a high content of polyphenylene ether or when it is used alone. In the present invention, since it contains a polyphenylene ether component having the rearrangement structure, the fluidity is improved to an extent that melt molding is possible, and it can be made into a melt extrusion molded product, and it is also possible to manufacture melt spun fibers, which are more difficult to manufacture. Each component of the present invention will be described below.
[0036] <Polyphenylene ether component> The polyphenylene ether component used in the present invention contains a polyphenylene ether having a rearrangement structure in which successive bonds at the ortho positions are bonded in repeating units in which successive bonds at the para positions are bonded.
[0037] The repeating units connected successively through the para-position bonds are preferably repeating units represented by the general formula (1), and the rearrangement structure preferably has a rearrangement structure represented by the general formula (2).
[0038] R in the general formulas (1) and (2) 1 , R 2 Examples of the alkyl group include a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, a pentyl group, a cyclopentyl group, a hexyl group, a cyclohexyl group, an octyl group, or a decyl group, an aryl group having 6 to 10 carbon atoms, such as a phenyl group, a 4-methylphenyl group, a 1-naphthyl group, or a 2-naphthyl group, and an aralkyl group having 7 to 10 carbon atoms, such as a benzyl group, a 2-phenylethyl group, or a 1-phenylethyl group.
[0039] When the hydrocarbon group has a substituent, examples of the substituent include a halogen atom such as a fluorine atom, an alkoxy group such as a methoxy group, etc. Specific examples of the hydrocarbon group having a substituent include a trifluoromethyl group, etc.
[0040] Among these, R 1 , R2 is preferably a hydrogen atom or a methyl group, and more preferably a hydrogen atom.
[0041] R in the general formulas (1) and (2) 3 Examples of the alkyl group include alkyl groups having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, a pentyl group, a cyclopentyl group, a hexyl group, a cyclohexyl group, an octyl group, and a decyl group; aryl groups having 6 to 10 carbon atoms, such as a phenyl group, a 4-methylphenyl group, a 1-naphthyl group, and a 2-naphthyl group; and aralkyl groups having 7 to 10 carbon atoms, such as a benzyl group, a 2-phenylethyl group, and a 1-phenylethyl group.
[0042] When the hydrocarbon group has a substituent, examples of the substituent include a halogen atom such as a fluorine atom, and an alkoxy group such as a methoxy group. Specific examples of the hydrocarbon group having a substituent include a trifluoromethyl group.
[0043] Among these, R 3 As the alkyl group, a methyl group is preferable.
[0044] R 3’ R 3 represents a divalent group in which one hydrogen atom has been removed, and is preferably a methylene group.
[0045] Specific examples of the repeating unit of the general formula (1) include repeating units derived from 2,6-dimethyl-1,4-phenylene ether, 2,6-diethyl-1,4-phenylene ether, 2-methyl-6-ethyl-1,4-phenylene ether, and 2,6-dipropyl-1,4-phenylene ether. Among these, the repeating unit derived from 2,6-dimethyl-1,4-phenylene ether is preferred.
[0046] The polyphenylene ether component having the rearrangement structure is preferably a homopolymer having a repeating unit of the general formula (1) or a copolymer containing two or more different repeating units of the general formula (1), which has the rearrangement structure represented by the general formula (2) in the copolymer.
[0047] The polyphenylene ether component having the rearrangement structure may contain a repeating unit other than the general formula (1) as long as it does not impair the effects of the present invention, and in that case, the rearrangement structure represented by the general formula (2) may be present in a copolymer containing the repeating unit of the general formula (1) and a repeating unit other than the general formula (1). The content of such a repeating unit other than the general formula (1) is not particularly limited as long as it does not impair the effects of the present invention, but for example, it is preferably about 5 mol % or less in the copolymer, and more preferably it is not contained at all.
[0048] The molecular weight of the polyphenylene ether having the rearrangement structure is not particularly limited, but the weight average molecular weight (Mw) is preferably 40,000 to 100,000, and more preferably 50,000 to 80,000. The number average molecular weight (Mn) is preferably 7,000 to 30,000, and more preferably 8,000 to 20,000. The molecular weight distribution (Mw / Mn) is preferably 3.5 to 8.0, and more preferably 4.0 to 6.0. The weight average molecular weight and number average molecular weight can be measured by the method described in the Examples.
[0049] The amount of rearrangement in the polyphenylene ether component having the rearrangement structure is not particularly limited, but is preferably 0.01 mol% or more, more preferably 0.05 mol% or more, even more preferably 0.1 mol% or more, and particularly preferably 0.15 mol% or more, based on the total polyphenylene ether structural units in the polyphenylene ether component. Furthermore, in order to obtain a fine fiber having a single yarn fineness of 15 dtex or less, it is preferably 2 mol% or more. In addition, the upper limit of the amount of rearrangement is not particularly limited, but is preferably 20 mol% or less, more preferably 18 mol% or less, even more preferably 5 mol% or less, and even more preferably 4 mol% or less. When the amount of rearrangement in the polyphenylene ether component having the rearrangement structure is within the above range, the fluidity is improved to a degree that allows melt molding, and it tends to be possible to form a melt extrusion molded product, which is preferable.
[0050] The rearrangement structure was confirmed by nuclear magnetic resonance spectroscopy ( 1 In H-NMR measurement, it is preferable that the polyphenylene ether shows peaks in the range of 3.8 to 4.0 ppm and in the range of 6.8 to 7.0 ppm. Usually, polyphenylene ether shows a peak in the vicinity of 6.4 to 6.6 ppm, which is a peak derived from hydrogen atoms at the 3- and 5-positions of the benzene ring in the polyphenylene ether main chain. The polyphenylene ether having the transition structure shows peaks in the range of 3.8 to 4.0 ppm and in the range of 6.8 to 7.0 ppm in addition to the peak in the vicinity of 6.4 to 6.6 ppm. The chemical shift in the range of 3.8 to 4.0 ppm is due to the R 3’ The chemical shift in the range of 6.8 to 7.0 ppm is due to the protons of a divalent group (e.g., a methylene group) represented by the formula: 1 , R 2 These are derived from protons of a group (for example, hydrogen atoms at the 3rd and 5th positions of a benzene ring bonded via a methylene group in the ortho position).
[0051] The polyphenylene ether component used in the present invention may contain a polyphenylene ether that does not have a rearrangement structure. Examples of the polyphenylene ether that does not have a rearrangement structure include a homopolymer having a repeating unit of the general formula (1), a copolymer containing two or more different repeating units of the general formula (1), and a copolymer having a repeating unit of the general formula (1) and a repeating unit other than the general formula (1). Examples of the content of the repeating unit of the general formula (1) or below in the copolymer include those mentioned above.
[0052] The polyphenylene ether component used in the present invention may contain a low molecular weight polyphenylene ether. The molecular weight of the low molecular weight polyphenylene ether may be, for example, a weight average molecular weight of about 2,000 to 8,000.
[0053] The content of the polyphenylene ether component is preferably 95% by mass or more, more preferably 98% by mass or more, and even more preferably substantially composed of only the polyphenylene ether component (100% by mass) in all the components forming the molded product. When the content of the polyphenylene ether component in the polyphenylene ether melt extrusion molded product is within the above range, the obtained molded product is excellent not only in mechanical strength but also in heat resistance, chemical resistance, flame retardancy, etc., and is therefore preferable.
[0054] <Ingredients other than polyphenylene ether ingredient> The polyphenylene ether melt extrusion molded product of the present invention may contain a resin component other than the polyphenylene ether component. Examples of the resin component other than the polyphenylene ether component include styrene, polyethylene, polypropylene, polyamides such as polyamide 4, polyamide 6, polyamide 10, polyamide 11, polyamide 66, polyamide 6T, and polyamide 6T / 11, polyesters such as polyethylene terephthalate and polybutylene terephthalate, and polycarbonates. However, the content is preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably none (0% by mass).
[0055] Furthermore, additives such as lubricants, plasticizers, antioxidants, ultraviolet absorbers, dulling agents, and antistatic agents can be added to the polyphenylene ether melt extrusion molded product of the present invention within the scope of not impairing the effects of the present invention.
[0056] <Polyphenylene ether melt extrusion molded product> The polyphenylene ether melt extrusion molded product of the present invention contains the polyphenylene ether component, and its production method is not particularly limited. For example, it can be produced by the production method of polyphenylene ether melt extrusion molded product described below.
[0057] The glass transition temperature of the polyphenylene ether melt extrusion molded product is not particularly limited, but is preferably from 190° C. to 210° C., more preferably from 190° C. to 208° C., and even more preferably from 200° C. to 205° C. Having a glass transition temperature in the above range is preferable because it allows a good balance between melt processability and heat resistance.
[0058] The polyphenylene ether melt extrusion molded product has a maximum stress of preferably 0.4 cN / dtex or more and 3.0 cN / dtex or less, more preferably 0.8 cN / dtex or more and 2.0 cN / dtex or less. The polyphenylene ether melt extrusion molded product has a maximum elongation of preferably 30% or more and 180% or less, more preferably 60% or more and 150% or less. The maximum stress and maximum elongation can be measured by the method described in the Examples.
[0059] The shape of the melt extrusion molded product is not particularly limited, and can be molded into various shapes such as pellets, films, sheets, plates, pipes, tubes, rods, fibers, nonwoven fabrics, paper, and fabrics. The polyphenylene ether component used in the present invention has excellent moldability, and can be made into polyphenylene ether melt spun fibers. The polyphenylene ether melt spun fibers have excellent high temperature stability. The polyphenylene ether melt spun fibers may be long fibers or short fibers.
[0060] <Polyphenylene ether melt-spun fiber> The single-filament fineness of the polyphenylene ether melt-spun fiber is preferably 1.0 dtex or more and 100 dtex or less, more preferably 1.0 dtex or more and 50 dtex or less, and even more preferably 1.0 dtex or more and 15 dtex or less, for applications such as general heat-resistant filters and heat-resistant woven fabrics. Such single-filament fineness can be appropriately set depending on the application. In the present invention, since the polyphenylene ether component having a specific rearrangement structure is contained, the flowability is improved, melt spinning is possible, and very fine fibers of 15 dtex or less can be obtained.
[0061] 2. Method for producing polyphenylene ether melt extrusion molding The method for producing a polyphenylene ether melt extrusion molded product of the present invention is characterized by comprising a step of melt extruding a raw material, polyphenylene ether, using an extruder equipped with a cylinder and a screw at a peripheral speed of the screw of 3.6 m / min or more.
[0062] The raw material polyphenylene ether may be a homopolymer having a repeating unit of the general formula (1), a copolymer containing two or more different repeating units of the general formula (1), or a copolymer having a repeating unit of the general formula (1) and a repeating unit other than the general formula (1). The content of the repeating unit other than the general formula (1) in the copolymer may be as described above. Among these, a homopolymer having a repeating unit of the general formula (1) is preferred.
[0063] Specific examples of homopolymers having a repeating unit of the general formula (1) include poly(2,6-dimethyl-1,4-phenylene ether), poly(2,6-diethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2,6-dipropyl-1,4-phenylene ether), and the like. Among these, poly(2,6-dimethyl-1,4-phenylene ether) is preferred.
[0064] As the poly(2,6-dimethyl-1,4-phenylene ether), commercially available products can also be suitably used. Specific examples include PPO640, PPO646, and PPOSA120 manufactured by SABIC Innovative Plastic, and ZYLON S201A and ZYLON S202A manufactured by Asahi Kasei Chemicals Corporation.
[0065] The glass transition temperature of the polyphenylene ether raw material is preferably 170° C. or higher, more preferably 200° C. or higher, and even more preferably 210° C. or higher. The upper limit of the glass transition temperature is not particularly limited, but is preferably 230° C. or lower. When the glass transition temperature of the polyphenylene ether raw material is in the above range, a polyphenylene ether molded product having high heat resistance can be obtained, which is preferable.
[0066] Furthermore, the raw material used in the present invention may contain two or more polyphenylene ethers having different glass transition temperatures, and specifically, in addition to the polyphenylene ether having a glass transition temperature of 170° C. or higher, it may contain a polyphenylene ether having a glass transition temperature of less than 170° C. By adding a polyphenylene ether having a glass transition temperature of less than 170° C., the melt viscosity is reduced and the fluidity is improved, but the amount of rearrangement in the polyphenylene ether tends to decrease.
[0067] In the raw material polyphenylene ether, the content of the polyphenylene ether having a glass transition temperature of 170° C. or higher is preferably 80% by mass or higher, more preferably 90% by mass or higher, and even more preferably 95% by mass or higher, and it is particularly preferable that the raw material polyphenylene ether is composed only of polyphenylene ether having a glass transition temperature of 170° C. or higher. The upper limit of the content of the polyphenylene ether having a glass transition temperature of 170° C. or higher is not particularly limited, but is preferably 100% by mass or lower. In the present invention, it is preferable to contain polyphenylene ether having a high glass transition temperature (i.e., high molecular weight) in the above range, because the resulting polyphenylene ether melt extrusion molded product has excellent mechanical strength, heat resistance, chemical resistance, flame retardancy, etc.
[0068] In addition, resin components other than the polyphenylene ether component and additives may be contained together with the polyphenylene ether raw material. The resin components other than the polyphenylene ether component and additives are as described above. The content of resin components other than the polyphenylene ether component in the raw material is preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably none (0% by mass).
[0069] As the extruder equipped with the cylinder and the screw, a single screw extruder or a twin screw extruder that can be generally used in this field can be used. In the present invention, it is preferable to use a twin screw extruder. The extruder is not limited to this, and any extruder that can effectively shear the polymer can be used.
[0070] The peripheral speed of the screw is required to cause the rearrangement reaction of the raw material polyphenylene ether, and is 3.6 m / min or more, preferably 3.7 m / min or more, and more preferably 3.8 m / min or more. The upper limit of the peripheral speed of the screw is not particularly limited, but is preferably 94.2 m / min or less. In the present invention, by increasing the screw rotation speed to make the peripheral speed of the screw 3.6 m / min or more, a high shear force can be applied to the raw material polyphenylene ether in the cylinder, and as a result, the molecular chain of the polyphenylene ether can be cut to form a polyphenylene ether having a rearrangement structure. The formation of the polyphenylene ether having the rearrangement structure makes it possible to melt extrusion mold the polyphenylene ether.
[0071] The shape of the screw is not particularly limited, and may be any shape that can apply a shearing force sufficient to cause a rearrangement reaction of the polyphenylene ether raw material.
[0072] If the temperature inside the cylinder is too low, the fluidity of the resin is poor, and if it is too high, the fluidity is improved, but foaming phenomenon occurs due to thermal decomposition of the resin, so it is necessary to select a processing temperature that balances these two. The temperature inside the cylinder is preferably, for example, 250 to 350°C, and more preferably 280 to 330°C. By setting the temperature inside the cylinder within the above range, it is preferable that polymer chain scission occurs easily while suppressing the foaming phenomenon.
[0073] When the polyphenylene ether melt extrusion molded product is a polyphenylene ether melt spun fiber, the method further comprises, after the melt extruding step, a step of discharging the molten polyphenylene ether from a spinning nozzle and spinning the same.
[0074] An example of the production of polyphenylene ether melt spun fibers will be described with reference to FIG. 1. The raw material polyphenylene ether is fed from a hopper 1 in FIG. 1 into an extruder 2 equipped with a cylinder and a screw, and the molten polyphenylene ether is metered at a discharge speed by a gear pump 3, passes through a filter medium 4 made of fine sand, and is discharged from a spinning nozzle 5 to obtain melt spun fibers. In addition, it is preferable to install a filter 6 made of a metal nonwoven fabric on the filter medium 4. By installing the filter 6, foreign matter can be removed in advance, and clogging of the filter medium 4 can be prevented, which is preferable.
[0075] From the viewpoint of preventing nozzle clogging due to oxidative crosslinking, it is preferable to provide a heat-retaining space 7 directly below the spinning nozzle 5 and introduce 8 an inert gas such as nitrogen into this region for spinning, and it is more preferable to introduce an inert gas heated by a heating torch 9. The temperature of the heated inert gas is preferably 100 to 500°C, and more preferably 200 to 400°C.
[0076] The spinning speed is not particularly limited and can be appropriately set depending on the required fineness, etc., but in order to stably obtain fine fibers, it is preferably about 100 to 400 m / min, and more preferably about 100 to 200 m / min.
[0077] The single hole output rate of the spinning nozzle is preferably 0.4 g / min or less, more preferably 0.3 g / min or less, and even more preferably 0.2 g / min or less. The lower limit of the single hole output rate is not particularly limited, but is preferably 0.05 g / min or more, more preferably 0.1 g / min or more, and even more preferably 0.12 g / min or more. By setting the single hole output rate within the above range, it is possible to obtain a fine polyphenylene ether fiber, which is preferable.
[0078] The single fiber fineness of the polyphenylene ether melt spun fiber obtained by the production method of the present invention can be appropriately set depending on the application of the fiber, but the production method of the present invention can obtain fine fibers of 15 dtex or less. This is because, in the present invention, a high shear force is applied to the raw material polyphenylene ether by melting at a very high screw rotation speed, which causes a rearrangement reaction in the raw material polyphenylene ether to form a polyphenylene ether having a rearrangement structure, resulting in improved fluidity and the production of melt spun fibers having the above single fiber fineness.
[0079] <Polyphenylene ether melt-spun short fibers> The polyphenylene ether melt spun staple fibers of the present invention can be obtained, for example, by doubling the polyphenylene ether melt spun fibers to form a tow, and cutting the resulting fiber.
[0080] The length of the polyphenylene ether melt-spun short fibers of the present invention is not particularly limited and can be appropriately adjusted depending on the application, but is usually 1 to 500 mm, preferably 3 to 400 mm, and more preferably 5 to 300 mm.
[0081] The tensile strength of the polyphenylene ether melt-spun short fiber of the present invention is not particularly limited, but is usually 0.8 to 60 cN / dtex, preferably 0.85 to 50 cN / dtex, and more preferably 0.9 to 40 cN / dtex. The tensile strength is measured in accordance with JIS L1013 8.5.1.
[0082] The tensile elongation of the polyphenylene ether melt spun short fiber of the present invention is not particularly limited, but is usually 30 to 180%, preferably 40 to 160%, and more preferably 60 to 150%. The tensile elongation is measured in accordance with JIS L1013 8.5.1.
[0083] The equilibrium moisture content of the polyphenylene ether melt-spun short fibers of the present invention is not particularly limited, but is usually 0.01 to 1.5%, preferably 0.02 to 1.2%, and more preferably 0.03 to 1.0%. The equilibrium moisture content is measured in accordance with JIS L1013.
[0084] The high temperature shrinkage of the polyphenylene ether melt spun short fiber of the present invention at 190°C is not particularly limited, but is usually 0.1 to 6%, preferably 0.3 to 5%, and more preferably 0.5 to 4%. The method for measuring the high temperature shrinkage at 190°C is described in the Examples.
[0085] The polyphenylene ether melt-spun staple fibers of the present invention are preferably flame-retardant staple fibers.
[0086] The flame-retardant short fibers can be obtained by subjecting the polyphenylene ether melt-spun short fibers to a flame-retardant treatment, for example, by heat-treating the polyphenylene ether melt-spun short fibers in air at 120 to 240°C for 1 to 30 hours to make them infusible (infusible treatment), and then heat-treating them in air at 260 to 400°C for 0.1 to 10 hours to make them flame-retardant (flame-retardant treatment).
[0087] In the infusibility treatment, the polyphenylene ether melt spun short fibers are treated in air at 120 to 240°C for 1 to 30 hours. Here, "in air" refers to an environment that is not particularly adjusted. The treatment temperature is 120 to 240°C, preferably 140 to 230°C, and more preferably 160 to 220°C. The treatment time is 1 to 30 hours, preferably 1.5 to 25 hours, and more preferably 2 to 20 hours. By setting the treatment time and temperature as described above, the polyphenylene ether melt spun short fibers do not melt in the subsequent flame retardant treatment, and an appropriate flame retardant treatment can be performed.
[0088] After the infusibility treatment, a flame-retardant treatment is performed in air at 260 to 400°C for 0.1 to 10 hours. "In air" refers to an environment that is not particularly adjusted. The treatment temperature is 260 to 400°C, preferably 270 to 380°C, and more preferably 280 to 360°C. The treatment time is 0.1 to 10 hours, preferably 0.3 to 8 hours, and more preferably 0.5 to 6 hours. By setting the treatment time and temperature as described above, a C=O bond structure is formed in the polyphenylene ether melt spun short fibers, and flame-retardant short fibers exhibiting extremely high flame retardancy, flame resistance, heat resistance, etc. are obtained.
[0089] The fineness of the flame-retardant staple fiber is not particularly limited and can be appropriately determined depending on the purpose for which the fiber is used, but for example, it is preferably 100 dtex or less, more preferably 95 dtex or less, and even more preferably 90 dtex or less. The fineness within the above range is preferable because it can be processed into various shapes such as woven fabrics, knitted fabrics, staple fiber nonwoven fabrics, paper, and cloth. In addition, the lower limit of the fineness is not particularly limited, but it is preferably 0.1 dtex or more, and more preferably 0.2 dtex or more.
[0090] The tensile strength of the flame-retardant short fiber is preferably 0.8 cN / dtex or more, more preferably 0.85 cN / dtex or more, and even more preferably 0.90 cN / dtex or more. The tensile strength in the above range is preferable because it improves the handleability of the fiber. The upper limit of the tensile strength is not particularly limited, but is preferably 50 cN / dtex or less, and more preferably 40 cN / dtex or less.
[0091] The polyphenylene ether melt spun staple fibers of the present invention can be used, for example, in paper, fabrics, heat-resistant binders, C / C composites, CFRP matrix resins, industrial brushes, and brake materials.
[0092] Paper formed from polyphenylene ether melt-spun fibers The paper of the present invention is formed from the polyphenylene ether melt spun fibers. The paper can be manufactured by a general method, for example, by a wet papermaking method. In the wet papermaking method, for example, an aqueous slurry containing the polyphenylene ether melt spun fibers is prepared, and then this aqueous slurry is subjected to a normal papermaking process. The aqueous slurry may contain a binder (for example, a water-soluble polymer fiber such as a polyvinyl alcohol fiber, or a heat-adhesive polymer fiber such as a polyethylene terephthalate fiber (PET fiber)). If necessary, the fibers used may be subjected to a beating process. In addition, in order to improve the uniformity and pressure adhesion of the paper, a heat pressing process may be added after the papermaking process.
[0093] The length of the polyphenylene ether melt spun fibers used in the production of paper is not particularly limited, but from the viewpoint of ensuring sufficient quality as paper, the length is preferably 0.5 mm or more, more preferably 1 mm or more, and is preferably 100 mm or less, more preferably 80 mm or less.
[0094] Depending on the purpose, the paper of the present invention may contain other fibers, various additives such as paper strength improvers, fixing agents, defoamers, dyes, ultraviolet absorbers, flame retardants, etc., and various fillers such as talc, kaolin, calcium carbonate, titanium dioxide, etc. These raw materials are often added to the aqueous slurry, but may also be attached by appropriate coating or the like.
[0095] Examples of other fibers include general-purpose fibers such as polyolefin fibers, polyester fibers, polyamide fibers, cellulose fibers, and polysulfone fibers; and heat-resistant fibers such as aromatic para-aramid, polyaryl ketone fibers, and polysulfone fibers.
[0096] The proportion of the polyphenylene ether melt spun fibers contained in the paper of the present invention is, for example, 50 to 100 mass%, preferably 55 to 98 mass%, more preferably 60 to 95 mass%, and even more preferably 65 to 90 mass%, from the viewpoints of mechanical strength, flame retardancy, heat resistance, high-temperature stability, chemical resistance, and the like.
[0097] The basis weight of the paper of the present invention is not particularly limited and can be appropriately adjusted depending on the application of the paper, but is usually 5 to 800 g / cm 2 and preferably 7 to 700 g / cm 2 , more preferably 10 to 600 g / cm 2 It is.
[0098] The tensile strength of the paper of the present invention is not particularly limited, but is usually 1 to 300 N / cm, preferably 3 to 250 N / cm, and more preferably 5 to 200 N / cm. The tensile strength is measured in accordance with JIS L1013 8.5.1.
[0099] The tensile elongation of the paper of the present invention is not particularly limited, but is usually 0.1 to 100%, preferably 0.3 to 90%, and more preferably 0.5 to 80%. The tensile elongation is measured in accordance with JIS L1013 8.5.1.
[0100] The LOI value of the paper of the present invention is not particularly limited, but is usually from 25 to 80, preferably from 27 to 75, and more preferably from 30 to 70. The LOI value is measured in accordance with JIS L 1091 E method.
[0101] The dielectric constant of the paper of the present invention is not particularly limited, but is usually from 1.0 to 2.9, preferably from 1.1 to 2.8, and more preferably from 1.2 to 2.7.
[0102] The equilibrium moisture content of the paper of the present invention is not particularly limited, but is usually 0.01 to 1.5%, preferably 0.02 to 1.2%, and more preferably 0.03 to 1.0%. The equilibrium moisture content is measured in accordance with JIS L1013.
[0103] The high temperature shrinkage of the paper of the present invention at 190° C. is not particularly limited, but is usually 0.1 to 20%, preferably 0.2 to 15%, and more preferably 0.3 to 10%. The method for measuring the high temperature shrinkage at 190° C. is described in the Examples.
[0104] The paper of the present invention is preferably a flame-retardant paper, which can be produced by the above-mentioned method using polyphenylene ether melt-spun fibers that have been subjected to the above-mentioned flame-retardant treatment.
[0105] The flame-resistant paper preferably has a weight loss rate difference of 5.0% or less between 150°C and 400°C, more preferably 4.0% or less, and even more preferably 3.5% or less. The weight loss rate difference within the above range is preferable because it suppresses polymer degradation and improves durability. The weight loss rate difference is preferably 0%, but usually there is a weight loss of about 0.1% or more, and may be about 0.15% or more.
[0106] The specific gravity of the flame-resistant paper is preferably 1.2 or more, more preferably 1.25 or more, and even more preferably 1.3 or more. The specific gravity being within the above range is preferable because the flame-resistant properties of the paper are sufficiently improved and the flame resistance is improved. The upper limit of the specific gravity is not particularly limited, but is preferably 2.0 or less, and more preferably 1.8 or less.
[0107] The LOI value of the flame-retardant paper is preferably 30 or more, more preferably more than 30, even more preferably 32 or more, and particularly preferably 35 or more. The LOI value being in the above range is preferable because the flame retardancy of the obtained flame-retardant paper is excellent. Here, the LOI value means the limiting oxygen index, and the higher the LOI value, the better the flame retardancy. Therefore, the higher the LOI value, the more preferable it is, and the upper limit is not particularly limited.
[0108] The tensile elongation of the flame-resistant paper is preferably 5% or more, more preferably 7% or more, and even more preferably 10% or more. The tensile elongation in the above range is preferable because it can improve processability. The upper limit of the tensile strength is not particularly limited, but is preferably 100% or less, and more preferably 80% or less.
[0109] The strength retention of the flame-resistant paper at 400°C is preferably 40% or more, more preferably 50% or more, and even more preferably 60% or more. The strength retention at 400°C within the above range is preferable because it provides high durability when used at high temperatures. The upper limit of the strength retention at 400°C is not particularly limited, but is preferably 100% or less, and more preferably 99% or less. Here, the strength retention at 400°C refers to the strength retention after heat treatment at 400°C for 10 minutes.
[0110] The elongation retention of the flame-resistant paper at 400°C is preferably 40% or more, more preferably 50% or more, and even more preferably 55% or more. The elongation retention at 400°C in the above range is preferable because it provides high durability when used at high temperatures. The upper limit of the elongation retention at 400°C is not particularly limited, but is preferably 100% or less, and more preferably 99% or less. Here, the elongation retention at 400°C refers to the elongation retention after heat treatment at 400°C for 10 minutes.
[0111] The paper of the present invention can be used, for example, as a heat insulating material, a sound absorbing material, a heat resistant filter, a heat resistant insulating paper, an electromagnetic wave shielding material, and the like.
[0112] <Fabrics formed from polyphenylene ether melt-spun fibers> The fabric of the present invention is formed from the polyphenylene ether melt-spun fibers. The fabric may further include one or more fibers selected from the group consisting of wholly aromatic polyester fibers, polybenzoxazole (PBO) fibers, polybenzimidazole (PBI) fibers, polybenzothiazole (PBTZ) fibers, polyimide (PI) fibers, polysulfonamide (PSA) fibers, polyetheretherketone (PEEK) fibers, polyetherimide (PEI) fibers, polyarylate (PAr) fibers, melamine fibers, phenolic fibers, fluorine-based fibers, polyphenylene sulfide (PPS) fibers, cellulose fibers, polyolefin fibers, acrylic fibers, rayon fibers, cotton fibers, animal hair fibers, polyurethane fibers, polyvinyl chloride fibers, polyvinylidene chloride fibers, acetate fibers, and polycarbonate fibers.
[0113] The proportion of the polyphenylene ether melt spun fibers contained in the fabric of the present invention is, for example, 50 to 100 mass%, preferably 55 to 98 mass%, more preferably 60 to 95 mass%, and even more preferably 65 to 90 mass%, from the viewpoints of mechanical strength, flame retardancy, heat resistance, high temperature stability, chemical resistance, and the like.
[0114] The fabric of the present invention may contain additives such as flame retardants, ultraviolet absorbing agents, reflectors, organic dyes, organic pigments, and inorganic pigments, as necessary.
[0115] The fabric of the present invention can be produced by a general method, for example, a method in which the spun yarn of the above-mentioned fiber is blended to obtain a spun yarn, and then the yarn is woven into a twill weave, plain weave, or other weave using a rapier loom or the like using a single yarn or a two-ply yarn.
[0116] The basis weight of the fabric of the present invention is not particularly limited and can be appropriately adjusted depending on the application of the fabric, but is usually 10 to 3000 g / cm. 2 and preferably 20 to 2500 g / cm 2 , more preferably 30 to 2000 g / cm 2 It is.
[0117] The LOI value of the fabric of the present invention is not particularly limited, but is usually from 25 to 80, preferably from 27 to 75, and more preferably from 30 to 70. The LOI value is measured in accordance with JIS L 1091 E method.
[0118] The high temperature shrinkage of the fabric of the present invention at 190° C. is not particularly limited, but is usually 0.1 to 20%, preferably 0.2 to 15%, and more preferably 0.3 to 10%. The method for measuring the high temperature shrinkage at 190° C. is as described in the Examples.
[0119] The fabric of the present invention is preferably a flame-retardant fabric. The flame-retardant fabric may be produced by using polyphenylene ether melt-spun fibers that have been subjected to the flame-retardant treatment by the above-mentioned method, or may be produced by using the polyphenylene ether melt-spun fibers to produce a fabric by the above-mentioned method, and then subjecting the produced fabric to the flame-retardant treatment.
[0120] The flame-resistant fabric preferably has a weight loss rate difference of 5.0% or less between 150°C and 400°C, more preferably 4.0% or less, and even more preferably 3.5% or less. The weight loss rate difference within the above range is preferable because it suppresses degradation of the polymer and improves durability. The weight loss rate difference is preferably 0%, but usually there is a weight loss of about 0.1% or more, and may be about 0.15% or more.
[0121] The specific gravity of the flame-resistant fabric is preferably 1.2 or more, more preferably 1.25 or more, and even more preferably 1.3 or more. The specific gravity being within the above range is preferable because the flame resistance of the fabric is sufficiently advanced and the flame resistance is improved. The upper limit of the specific gravity is not particularly limited, but is preferably 2.0 or less, and more preferably 1.8 or less.
[0122] The LOI value of the flame-resistant fabric is preferably 30 or more, more preferably more than 30, even more preferably 32 or more, and particularly preferably 35 or more. The LOI value in the above range is preferable because the flame retardancy of the obtained flame-resistant fabric is excellent. Here, the LOI value means the limiting oxygen index, and the larger the LOI value, the better the flame retardancy. Therefore, the larger the LOI value, the more preferable it is, and the upper limit value is not particularly limited.
[0123] The tensile elongation of the flame-resistant fabric is preferably 5% or more, more preferably 7% or more, and even more preferably 10% or more. The tensile elongation in the above range is preferable because it can improve processability. The upper limit of the tensile strength is not particularly limited, but is preferably 100% or less, and more preferably 80% or less.
[0124] The strength retention of the flame-resistant fabric at 400°C is preferably 40% or more, more preferably 50% or more, and even more preferably 60% or more. The strength retention at 400°C in the above range is preferable because it provides high durability when used at high temperatures. The upper limit of the strength retention at 400°C is not particularly limited, but is preferably 100% or less, and more preferably 99% or less. Here, the strength retention at 400°C refers to the strength retention after heat treatment at 400°C for 10 minutes.
[0125] The elongation retention of the flame-resistant fabric at 400°C is preferably 40% or more, more preferably 50% or more, and even more preferably 55% or more. The elongation retention at 400°C in the above range is preferable because it provides high durability when used at high temperatures. The upper limit of the elongation retention at 400°C is not particularly limited, but is preferably 100% or less, and more preferably 99% or less. Here, the elongation retention at 400°C refers to the elongation retention after heat treatment at 400°C for 10 minutes.
[0126] The fabric of the present invention can be used, for example, as a heat insulating material, workwear (for firefighters, racers, and pilots), heat-resistant gloves, disaster prevention hoods, interior materials for transport equipment, heat-resistant clothing, and electromagnetic wave shielding materials.
[0127] <Film> The polyphenylene ether melt extrusion molded product of the present invention is preferably a film. The film can be produced by the above-mentioned method.
[0128] The elastic modulus of the film is not particularly limited, but is usually from 1000 to 4500 MPa, preferably from 1200 to 4000 MPa, and more preferably from 1500 to 3500 MPa. The elastic modulus is measured in accordance with JIS K7127.
[0129] The maximum point stress of the film is not particularly limited, but is usually 30 to 300 MPa, preferably 40 to 250 MPa, and more preferably 50 to 200 MPa. The maximum point stress is measured in accordance with JIS K7127.
[0130] The breaking strain of the film is not particularly limited, but is usually 1 to 100%, preferably 3 to 80%, and more preferably 5 to 70%. The breaking strain is measured in accordance with JIS K7127.
[0131] The dielectric constant of the film is not particularly limited, but is usually 1.8 to 3.2, preferably 1.9 to 3.1, and more preferably 2.0 to 3.0. The dielectric constant is measured in accordance with JIS C2565.
[0132] The dielectric loss tangent of the film is not particularly limited, but is usually 0.0003 to 0.02, preferably 0.0005 to 0.015, and more preferably 0.001 to 0.01. The dielectric constant is measured in accordance with JIS C2565.
[0133] The film is preferably a flame-resistant film.
[0134] The flame-resistant film is obtained by subjecting the film to the flame-resistant treatment.
[0135] The elastic modulus of the flame-resistant film is not particularly limited, but is usually 1500 to 5500 MPa, preferably 2000 to 5000 MPa, and more preferably 2500 to 4500 MPa. The elastic modulus is measured in accordance with JIS K7127.
[0136] The maximum point stress of the flame-resistant film is not particularly limited, but is usually 1 to 40 MPa, preferably 2 to 30 MPa, and more preferably 3 to 25 MPa. The maximum point stress is measured in accordance with JIS K7127.
[0137] The breaking strain of the flame-resistant film is not particularly limited, but is usually 1 to 50%, preferably 2 to 40%, and more preferably 3 to 30%. The breaking strain is measured in accordance with JIS K7127.
[0138] The dielectric constant of the flame-resistant film is not particularly limited, but is usually 2.0 to 3.6, preferably 2.2 to 3.4, and more preferably 2.4 to 3.2. The dielectric constant is measured in accordance with JIS C2565.
[0139] The dielectric loss tangent of the flame-resistant film is not particularly limited, but is usually 0.003 to 0.03, preferably 0.004 to 0.025, and more preferably 0.005 to 0.02. The dielectric constant is measured in accordance with JIS C2565.
[0140] The film of the present invention can be used, for example, as an FPC substrate, a coverlay, an adhesive tape substrate, a release film for molding laminated substrates, a transparent heat-resistant protective film, a special release film for heat-resistant substrates, and the like. EXAMPLES
[0141] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The methods for evaluating physical properties and the like in the following examples are as follows.
[0142] (1) Fineness, single yarn fineness The measurement was performed according to the method described in JIS L-1095 9.4.1. The single yarn fineness was calculated by dividing the fineness by the number of filaments.
[0143] (2) Maximum stress and maximum elongation Measurements were made in accordance with JIS L1013 8.5.1. The stress at the maximum load was taken as the maximum point stress, and the elongation at the maximum load was taken as the maximum point elongation.
[0144] (3) Glass transition temperature Using a differential scanning calorimeter (model: DSC-Q100) manufactured by TA Instruments, 2 mg of the molded body (fiber) was measured in a nitrogen atmosphere from 30°C to 250°C at a heating rate of 10°C / min, and the temperature at the intersection of the extension of the baseline below the glass transition temperature and the tangent showing the maximum slope at the transition section was taken as the glass transition temperature (Tg).
[0145] (4) Amount of dislocation structure in the compact Resonance frequency 600MHz 1 The measurement was performed by H-NMR measurement. The measurement was performed using an NMR device manufactured by BRUKER (device name: AVANCE-NEO600) as follows. 10 mg of the molded body (sample) obtained in the examples and comparative examples was dissolved in deuterated chloroform, and the solution was filled into an NMR tube within 2 hours and measured. Deuterated chloroform was used as the lock solvent, the waiting time was 1 second, the data acquisition time was 4 seconds, and the number of integrations was 64. Moreover, deuterated benzene may be used as the solvent. The analysis of the amount of dislocation structure was carried out as follows. Polyphenylene ether R at 3 and 5 positions 1 , R 2 The peaks due to the protons of the R group and the R 3’ The peak integral values of the peaks derived from the protons of the divalent group (such as a methylene group) represented by the following formula were taken as A and B, and the amount of rearrangement structure was calculated by the following formula. Amount of rearrangement structure (mol%) = (B / (A+B)) × 100
[0146] (5) Weight average molecular weight (Mw), number average molecular weight (Mn) The measurement device used was HLC-8320GPC manufactured by Tosoh Corporation. Two TSKgel SuperHM-H columns and a TSKgel SuperH2000 column were connected in series. Chloroform was used as the mobile phase, the flow rate was 0.6 ml / min, and the temperature of the column oven was 40°C. A chloroform solution with a concentration of 1 g / L was prepared from the molded product and the measurement was performed. The weight average molecular weight and number average molecular weight were calculated by creating a calibration curve using standard polystyrene. The UV wavelength of the detector was 283 nm for the evaluation object and 254 nm for the standard polystyrene. In Examples 1 to 7 and Comparative Example 2, the measurement was performed using a discharged thread (a thread obtained by allowing a polymer discharged from a nozzle to fall freely) as the "molded product".
[0147] (6) Screw peripheral speed The peripheral speed of the screw was calculated by the following formula. Screw peripheral speed (m / min) = screw diameter (mm) x 0.00314 x screw rotation speed (rpm)
[0148] <Polyphenylene ether melt-spun fiber> Example 1 Poly(2,6-dimethyl-1,4-phenylene ether) (PPO640, glass transition temperature (Tg): 221°C, manufactured by SABIC Innovative Plastic) was extruded using a twin-screw extruder (product name: KZW15TW-30MG) manufactured by Technobel Co., Ltd. The twin-screw extruder had four cylinder zones, and the cylinders were designated as cylinders 1, 2, 3, and 4 from the hopper side, with cylinders 1 to 3 set to 280°C, cylinder 4 and the cylinder head set to 300°C, the screw rotation speed was set to 700 rpm, and the screw peripheral speed was set to 33.0 m / min.
[0149] A gear pump was installed downstream of the extruder to measure the polymer discharge rate, and the polymer was extruded through a metal nonwoven filter (product name: NF-07, manufactured by Nippon Seisen Co., Ltd.) to a nozzle (nozzle hole diameter: 0.23 mm, nozzle hole land length: 0.3 mm, number of nozzle holes: 24) (total discharge amount: 3.5 g / min, single hole discharge amount: 0.146 g / min). A surface heater was placed directly below the nozzle, and the nozzle temperature was set to 316°C. A 60 mm heat retention space was provided directly below the nozzle, and nitrogen heated to 300°C was continuously introduced into this area. The polymer discharged from the nozzle was wound up at a spinning speed of 100 m / min. The fineness of the obtained melt spun fiber was 355 dtex, the single yarn fineness was 14.8 dtex, the maximum point stress was 0.95 cN / dtex, the maximum point elongation was 92.9%, and the glass transition temperature was 204°C. The amount of rearrangement structures in the obtained fibers was 2.8 mol% based on the total PPE units.
[0150] The obtained fiber was measured based on the measurement method of "(4) Amount of rearrangement structures in the molded body (fiber)" above. 1 H-NMR measurement was performed. As a result, when deuterated chloroform was set to 7.28 ppm, peaks were observed around 6.9 ppm, around 6.48 ppm, and around 3.87 ppm. The peak around 6.9 ppm corresponds to the protons at the 3rd and 5th positions of the polyphenylene ether generated by rearrangement (i.e., in the rearranged structure), the peak around 6.48 ppm corresponds to the protons at the 3rd and 5th positions of the polyphenylene ether in the main chain, and the peak around 3.87 ppm corresponds to the methylene of the methylene bridge generated by rearrangement. When deuterated benzene was used as the solvent, peaks were observed at around 6.8 ppm and 3.7 ppm when the deuterated benzene concentration was 7.1 ppm. The peak at around 6.9 ppm corresponds to the protons at the 3- and 5-positions of the polyphenylene ether generated by rearrangement (i.e., in the rearranged structure), and the peak at around 3.7 ppm corresponds to the methylene protons of the methylene bridge generated by rearrangement.
[0151] Examples 2 to 6 Melt spun fibers were obtained in the same manner as in Example 1, except that the screw rotation speed, screw peripheral speed, nozzle shape, and spinning conditions were changed as shown in Table 1. The fiber properties and discharged yarn characteristics of the obtained fibers are shown in Table 1.
[0152] Example 7 A blend of 90 parts of poly(2,6-dimethyl-1,4-phenylene ether) (PPO640, glass transition temperature (Tg): 221°C, manufactured by SABIC Innovative Plastic) and 10 parts of poly(2,6-dimethyl-1,4-phenylene ether) (PPOSA120, glass transition temperature (Tg): 159°C, manufactured by SABIC Innovative Plastic) was used, and melt spun fibers were obtained in the same manner as in Example 1, except that the spinning conditions were changed as shown in Table 1. The fiber properties and discharged yarn characteristics of the obtained fibers are shown in Table 1.
[0153] Example 8 Except for changing the peripheral speed of the screw to 3.8 m / min, melt spun fibers were obtained in the same manner as in Example 5. The fiber properties and discharged yarn characteristics of the obtained fibers are shown in Table 1.
[0154] Comparative Example 1 In Comparative Example 1, melt spun fibers were produced in the same manner as in Example 1, except that the screw rotation speed was 50 rpm, i.e., the peripheral speed of the screw was 2.4 m / min. However, the viscosity was too high to extrude the polymer from the gear pump, resulting in damage to the gear pump.
[0155] Comparative Example 2 A mixture of 80 parts of poly(2,6-dimethyl-1,4-phenylene ether) (PPO640, manufactured by SABIC Innovative Plastic) and 20 parts of polystyrene (679, manufactured by PS Japan Co., Ltd.) was used, and melt spinning was performed in the same manner as in Example 1, except that the spinning conditions were changed as shown in Table 1. However, the spinnability was very poor, and it was only by increasing the single-hole output rate to 0.242 g / min that a fiber with a single yarn fineness of 78.4 dtex could be obtained at a spinning speed of 30 m / min. The fiber properties and discharged yarn characteristics of the obtained fiber are shown in Table 1.
[0156] [Table 1]
[0157] In Table 1, "640" stands for poly(2,6-dimethyl-1,4-phenylene ether) (PPO640, glass transition temperature (Tg): 221°C, manufactured by SABIC Innovative Plastic), "SA120" stands for poly(2,6-dimethyl-1,4-phenylene ether) (PPOSA120, glass transition temperature (Tg): 159°C, manufactured by SABIC Innovative Plastic), and "PS(679)" stands for polystyrene (679, manufactured by PS Japan Co., Ltd.).
[0158] As shown in Table 1, in the examples of the present invention, although only poly(2,6-dimethyl-1,4-phenylene ether) was used, the screw circumferential speed was high and strong shear force was applied, so that a rearrangement structure was generated and melt spun fibers were obtained. In particular, in Examples 3 and 4, thin fibers with single yarn finenesses of 6.6 dtex and 5.1 dtex were obtained. In addition, the melt spun fibers obtained in the examples were excellent in maximum point stress and elongation at break. In contrast, in Comparative Example 1, melt spun fibers could not be obtained. This is considered to be because in Comparative Example 1, the screw circumferential speed was low and the shear force was insufficient, so that a rearrangement structure was not formed in the polyphenylene ether, and the viscosity was too high to extrude the polymer from the gear pump. In Comparative Example 2, although polystyrene was blended with poly(2,6-dimethyl-1,4-phenylene ether), the spinnability was very poor and only very thick fibers could be obtained. In addition, the obtained fibers had low strength, elongation, and glass transition temperature.
[0159] <Polyphenylene ether melt-spun short fibers> Example 9 The melt spun fibers obtained in Example 1 were doubling to form a tow, which was then cut into short fibers having a fiber length of 50 mm using a guillotine cutter.
[0160] (1) Tensile strength and elongation Measurements were made in accordance with JIS L1013 8.5.1. The stress at the maximum load was taken as the tensile strength, and the elongation at the maximum load was taken as the tensile elongation.
[0161] (2) High temperature shrinkage rate The fiber length (X cm) of a 5 cm-long short fiber cut out from the fiber without fixing the ends was measured after storing the fiber for 10 minutes in an air thermostatic chamber maintained at 190°C. The fiber length was calculated using the following formula. However, if it is not possible to obtain a 5 cm-long short fiber, the length may be changed as necessary. High temperature shrinkage rate (%) = <x 5>×100 (When 5 cm short fibers cannot be obtained, <X / length before treatment> × 100)
[0162] (3) Equilibrium moisture content In accordance with JIS L1013, after the sample was dried to absolute dryness in an atmosphere of 120 °C, it was adjusted for 72 hours at a temperature of 20 °C and a relative humidity of 65% RH, and the moisture content contained in the sample with respect to the mass of the sample in the absolute dry state was calculated and expressed as a percentage (%).
[0163]
Table 2
[0164] <Flame-retardant short fiber> Example 10 The melt-spun fibers obtained in Example 1 were combined into a bundle and cut into 50 mm fiber lengths with a guillotine cutter to obtain short fibers. The obtained short fibers were heat-treated in an air atmosphere in the order of 200 °C × 120 min, 210 °C × 20 min, 220 °C × 20 min, 250 °C × 120 min, 280 °C × 120 min, 320 °C × 120 min to produce flame-retardant short fibers.
[0165] (1) Tensile strength, elongation at break Measured in accordance with JIS L1013 8.5.1. The stress at the maximum load was defined as the tensile strength, and the elongation rate at the maximum load was defined as the elongation at break.
[0166] (2) High-temperature shrinkage rate The flame-retardant short fibers cut to 5 cm were held in an air constant-temperature bath maintained at 190 °C for 10 minutes without fixing the ends, and then calculated using the following formula from the fiber length (X cm). However, when 5 cm flame-retardant short fibers cannot be obtained, the measurement may be performed by appropriately changing the length. High-temperature shrinkage rate (%) = <x 5>×100 (When the 5 cm flame-retardant short fibers cannot be obtained, <X / length before treatment> × 100)
[0167] (3) Equilibrium moisture content In accordance with JIS L1013, the sample was dried to absolute dryness in an atmosphere of 120 °C, then adjusted for 72 hours at a temperature of 20 °C and a relative humidity of 65%RH. The moisture content contained in the sample with respect to the mass of the sample in the absolute dry state was calculated and expressed as a percentage (%).
[0168] (4) Generated gas Measured in accordance with STM E662.
[0169] (5) Smoke generation amount Measured in accordance with BSS 7239.
[0170]
Table 3
[0171] <Paper formed from polyphenylene ether melt-spun fibers> Example 11 The melt-spun fibers obtained in Example 1 were combined into a bundle and cut into short fibers with a fiber length of 5 mm using a guillotine cutter. The obtained short fibers were used for wet papermaking. During papermaking, the surfactant "Maker Surfactant MK-37" manufactured by Meisei Chemical Industry Co., Ltd. was used. The obtained paper sheet was placed on an aluminum foil and washed with approximately 5 L of ion-exchanged water using a spray. Then, it was sandwiched between aluminum foils and calendered at a temperature of 210 °C, a linear pressure of 30 kg / cm (calculated as a 25 cm width), and a roller speed of 1.0 m / min to produce a paper (basis weight: 320 g / cm 2 )
[0172] (1) Tensile strength, elongation at break Measured in accordance with JIS L1013 8.5.1. Using a sample with a width of 25 mm and a length of 100 mm, the distance between chucks was 50 mm, and the tensile speed was 100 mm / min. The elongation at break was defined as the elongation when the strength reached its maximum.
[0173] (2) LOI value Measurements were made in accordance with JIS L 1091 E. The oxygen index was determined when the flame continued to burn for 50 mm or more, and the heat source for the igniter was propane gas.
[0174] (3) Dielectric constant A 50 μm thick sample was measured using a dielectric constant measuring device manufactured by AET Corporation in accordance with JIS C2565 using the cavity resonator method (TM mode). The frequency was 10 GHz. The sample size was 3 mm wide and 80 mm long.
[0175] (4) Equilibrium moisture content In accordance with JIS L1013, the samples were dried in an atmosphere at 120°C, and then conditioned at a temperature of 20°C and a relative humidity of 65%RH for 72 hours. The moisture content of the samples relative to the mass of the samples in the dried state was calculated and expressed as a percentage (%).
[0176] (5) High temperature shrinkage rate The length of the paper (X cm) after cutting the paper into a 10 cm square and leaving the ends unfixed in an air thermostatic chamber kept at 190°C for 10 minutes was calculated using the following formula. High temperature shrinkage rate (%) = <x 10>×100
[0177] [Table 4]
[0178] <Flame-retardant paper> Example 12 The paper produced in Example 11 was heat-treated in an air atmosphere in the following order: 200°C x 120 min, 210°C x 20 min, 220°C x 20 min, 250°C x 120 min, 280°C x 120 min, and 320°C x 120 min to produce flame-resistant paper.
[0179] (1) Tensile strength and elongation Measurements were made in accordance with JIS L1013 8.5.1. Samples 25 mm wide and 100 mm long were used, with a chuck distance of 50 mm and a tensile speed of 100 mm / min. The tensile elongation was defined as the elongation at which the strength was at its maximum.
[0180] (2) Gas generated Measured in accordance with STM E662.
[0181] (3) Amount of smoke produced Measured in accordance with BSS 7239.
[0182] (4) LOI value Measurements were made in accordance with JIS L 1091 E. The oxygen index was determined when the flame continued to burn for 50 mm or more, and the heat source for the igniter was propane gas.
[0183] (5) Dielectric constant A 50 μm thick sample was measured using a dielectric constant measuring device manufactured by AET Corporation in accordance with JIS C2565 using the cavity resonator method (TM mode). The frequency was 10 GHz. The sample size was 3 mm wide and 80 mm long.
[0184] (6) Equilibrium moisture content In accordance with JIS L1013, the samples were dried in an atmosphere at 120°C, and then conditioned at a temperature of 20°C and a relative humidity of 65%RH for 72 hours. The moisture content of the samples relative to the mass of the samples in the dried state was calculated and expressed as a percentage (%).
[0185] (7) High temperature shrinkage rate The flame-retardant paper was cut into 10 cm square pieces and left in an air thermostatic chamber kept at 190°C for 10 minutes without fixing the ends. The paper length (X cm) was then calculated using the following formula. High temperature shrinkage rate (%) = <x 10>×100
[0186] [Table 5]
[0187] <Fabrics formed from polyphenylene ether melt-spun fibers> Example 13 The melt-spun fibers obtained in Example 1 were woven to obtain a fabric with a basis weight of 150 g / m 2 Thus, a plain weave fabric of 100 g was obtained.
[0188] (1) LOI value Measurements were made in accordance with JIS L 1091 E. The oxygen index was determined when the flame continued to burn for 50 mm or more, and the heat source for the igniter was propane gas.
[0189] (2) High temperature shrinkage rate The fabric was cut into a 10 cm square and held in an air thermostatic chamber kept at 190° C. for 10 minutes without fixing the ends. The fabric length (X cm) was calculated using the following formula. High temperature shrinkage rate (%) = <x 10>×100
[0190] [Table 6]
[0191] <Flame resistant fabric> Example 14 The plain weave fabric produced in Example 13 was heat treated in an air atmosphere in the following order: 200°C x 120 min, 210°C x 20 min, 220°C x 20 min, 250°C x 120 min, 280°C x 120 min, and 320°C x 120 min to produce a flame-resistant fabric.
[0192] (1) Gas generated Measured in accordance with STM E662.
[0193] (2) Amount of smoke produced Measured in accordance with BSS 7239.
[0194] (3) LOI value Measurements were made in accordance with JIS L 1091 E. The oxygen index was determined when the flame continued to burn for 50 mm or more, and the heat source for the igniter was propane gas.
[0195] (4) High temperature shrinkage rate The flame-resistant fabric was cut into a 10 cm square and held in an air thermostatic chamber kept at 190°C for 10 minutes without fixing the ends. The fabric length (X cm) was calculated using the following formula. High temperature shrinkage rate (%) = <x 10>×100
[0196] [Table 7]
[0197] <Melted polyphenylene ether film> Example 15 Poly(2,6-dimethyl-1,4-phenylene ether) (PPO640, glass transition temperature (Tg): 221°C, manufactured by SABIC Innovative Plastic) was extruded using a twin-screw extruder (product name: KZW15TW-45MG) manufactured by Technovel Co., Ltd. The twin-screw extruder was set to 300°C, the screw rotation speed was set to 700 rpm, and the peripheral speed of the screw was set to 33.0 m / min. A gear pump was installed downstream of the extruder to measure the polymer discharge rate, and the polymer was extruded at a discharge rate of 22.5 g / min into a T-die (TDS / 150-SGI) manufactured by Technobel Co., Ltd. The polymer extruded from the T-die was taken up at a take-up speed of 3 m / min on a roll (FPU-200-SGI) manufactured by Technobel Co., Ltd. to produce a molten polyphenylene ether film.
[0198] Comparative Example 3 In Comparative Example 3, an attempt was made to produce a film in the same manner as in Example 15, except that the screw rotation speed was 50 rpm, i.e., the peripheral speed of the screw was 2.4 m / min. However, the viscosity was too high to extrude the polymer from the gear pump, and a film could not be produced.
[0199] (1) Elastic modulus, maximum stress, and breaking strain The elastic modulus in the MD direction of the film, the maximum stress, and the breaking strain were measured at 23°C in accordance with JIS K7127.
[0200] (2) Dielectric constant and dielectric tangent The dielectric constant of a 50 μm-thick film was measured using a dielectric constant measuring device manufactured by AET Corporation in accordance with JIS C2565 by the cavity resonator method (TM mode). The frequency was 10 GHz. The sample size was 3 mm wide and 80 mm long.
[0201] [Table 8]
[0202] <Flame-retardant film> Example 16 The molten polyphenylene ether film produced in Example 15 was heat-treated in an air atmosphere in the following order: 200°C x 120 min, 210°C x 20 min, 220°C x 20 min, 250°C x 120 min, 280°C x 120 min, and 320°C x 120 min to produce a flame-resistant film.
[0203] (1) Elastic modulus, maximum stress, and breaking strain The elastic modulus in the MD direction, the maximum stress, and the breaking strain of the flame-resistant film were measured at 23°C in accordance with JIS K7127.
[0204] (2) Dielectric constant and dielectric tangent The dielectric constant of a 50 μm-thick flame-resistant film was measured using a dielectric constant measuring device manufactured by AET Corporation in accordance with JIS C2565 using the cavity resonator method (TM mode). The measurement was performed at a frequency of 10 GHz. The sample size was 3 mm wide and 80 mm long.
[0205] [Table 9] [Explanation of symbols]
[0206] 1 Hopper 2. Extruder 3. Gear pump 4. Filters 5. Spinning nozzle 6 Filter media 7. Insulation space 8. Introduction of inert gas 9 Heating Torch< / x> < / x> < / x> < / x> < / x> < / x>
Claims
1. A polyphenylene ether melt extrudate comprising a polyphenylene ether component, the polyphenylene ether component is a polyphenylene ether component having a rearrangement structure in which successive bonds at ortho positions are bonded in repeating units in which successive bonds at para positions are bonded (however, a polyphenylene ether component modified with a styrene-based compound is excluded); The content of the polyphenylene ether component is 95% by mass or more based on all components forming the molded body, the amount of rearrangements in the polyphenylene ether component having a rearrangement structure is 0.05 mol % or more based on the total polyphenylene ether structural units in the polyphenylene ether component, The polyphenylene ether melt extrusion molded product is a film (however, excluding those containing a polytetrafluoroethylene-containing mixed powder consisting of polytetrafluoroethylene particles having a particle size of 10 μm or less and an organic polymer, excluding those containing an organic phosphate ester-based flame retardant, and excluding those containing a cage-shaped silsesquioxane partially cleaved structure).
2. The repeating units connected consecutively at the para position are represented by the following general formula (1): 【Chemistry 1】 (In the formula, R 1 , R 2 are each independently a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent; R 3 each independently represents a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, and the rearrangement structure is a repeating unit represented by the following general formula (2): 【Chemistry 2】 (In the formula, R 1 , R 2 are each independently a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent; R 3 each independently represents a hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, R 3’ is the R 3 2. The polyphenylene ether melt extrusion molded product according to claim 1, wherein the structure is represented by the following formula (III):
3. The rearrangement structure is shown by nuclear magnetic resonance spectrum ( 1 3. The polyphenylene ether melt extrusion molded product according to claim 1, which shows peaks in the range of 6.8 to 7.0 ppm and in the range of 3.8 to 4.0 ppm in H-NMR measurement.
4. 4. The polyphenylene ether melt-extrusion molded product according to claim 1, which has a glass transition temperature of 190° C. or higher and 210° C. or lower.
5. 2. The polyphenylene ether melt extrusion molded product according to claim 1, wherein the film is a flame-retardant film.
6. A method for producing a polyphenylene ether melt extrusion product containing a polyphenylene ether component, comprising the steps of: The method includes a step of melt-extruding a raw material polyphenylene ether using an extruder equipped with a cylinder and a screw at a peripheral speed of the screw of 3.6 m / min or more, the polyphenylene ether component is a polyphenylene ether component having a rearrangement structure in which successive bonds at ortho positions are bonded in repeating units in which successive bonds at para positions are bonded (however, a polyphenylene ether component modified with a styrene-based compound is excluded); The content of the polyphenylene ether component is 95% by mass or more based on all components forming the molded body, the amount of rearrangements in the polyphenylene ether component having a rearrangement structure is 0.05 mol % or more based on the total polyphenylene ether structural units in the polyphenylene ether component, A method for producing a polyphenylene ether melt extrusion molded product (excluding those containing a polytetrafluoroethylene-containing mixed powder consisting of polytetrafluoroethylene particles with a particle diameter of 10 μm or less and an organic polymer, excluding those containing an organic phosphate ester-based flame retardant, and excluding those containing a cage-shaped silsesquioxane partially cleaved structure), characterized in that the polyphenylene ether melt extrusion molded product is a film.
7. 7. The method for producing a polyphenylene ether melt extrusion molded product according to claim 6, wherein the temperature inside the cylinder is 250 to 350°C.
8. 8. The method for producing a polyphenylene ether melt extrusion molded product according to claim 6, wherein the raw material polyphenylene ether contains a polyphenylene ether having a glass transition temperature of 170° C. or higher.
9. 9. The method for producing a polyphenylene ether melt extrusion molded product according to claim 8, wherein the raw material polyphenylene ether further contains a polyphenylene ether having a glass transition temperature of less than 170°C.
Citation Information
Patent Citations
Polyphenylene ether resin composition excellent in appearance and its production
JP1995242791A
Polyphenylene ether-based resin composition
JP2000281893A
Polyphenylene ether formulation with high fluidity
JP2003531234A
Resin composition and method for producing the same
JP2004107511A
Fiber, fiber assembly and molding of fiber assembly
JP2004190156A